Review of agricultural spraying technologies for plant protection using unmanned aerial vehicle (UAV) - Chen, Haibo; Lan, Yubin; Fritz, Bradley K; Hoffmann, W. Clint; Liu, Shengbo (International Journal of Agricultural and Biological Engineering, 2021)
With changing climate and farmland ecological conditions, pest outbreaks in agricultural landscapes are becoming more frequent, increasing the need for improved crop production tools and methods. UAV-based agricultural spraying is anticipated to be an important new technology for providing efficient and effective applications of crop protection products. This paper reviews and summarizes the status of the current research and progress on UAV application technologies for plant protection, and it discusses the characteristics of atomization by unmanned aircraft application systems with a focus on spray applications of agrichemicals. Additionally, the factors influencing the spraying performance including downwash airflow field and operating parameters are analyzed, and a number of key technologies for reducing drift and enhancing the application efficiency such as remote sensing, variable-rate technologies, and spray drift models are considered. Based on the reviewed literature, future developments and the impacts of these UAV technologies are projected. This review may inspire the innovation of the combined use of big data analytics and UAV technology, precision agricultural spraying technology, drift reduction technology, swarm UAV cooperative technology, and other supporting technologies for UAV-based aerial spraying for scientific research in the world.Keywords: UAV, plant protection, spraying technology, drift reduction, pesticide efficacy, spraying model, big data analyticsDOI: 10.25165/j.ijabe.20211401.5714Citation: Chen H B, Lan Y B, Fritz B K, Hoffmann W C, Liu S B. Review of agricultural spraying technologies for plant protection using unmanned aerial vehicle (UAV). Int J Agric & Biol Eng, 2021; 14(1): 38–49.